TELAAH KEBUTUHAN MEDIA PEMBELAJARAN BAHASA MADURA DI SEKOLAH MENENGAH PERTAMA - Kusyairi Kusyairi; M. Khoiri (Kantor Bahasa Provinsi Maluku Utara, 2021)
This study aims to examine the need assessment of the Madurese language learning media based on the responses of junior high school teachers. Based on the results of questionnaire collection that is analyzed with quantitative descriptions, the researcher concluded that the characteristics of the students are mostly active and they are interested in learning the Madurese.The use of learning methods is good, then the teachers must use more varied methods.Many teachers use textbook media and a little other media (multimedia) and even then mostly only occasionally. Teachers want adequate references and facilities to implement Madurese learning media and special training for Madurese language teachers. The teachers also suggest that there should bemany and widely available learning media, according to standardized spelling of the curriculum, and the free internet (wifi) to ease the learning and teaching Madurese.